A CASE STUDY OF A THREE-YEAR-OLD BOY'S PERLOCUTIONARY ACTS TO INDIRECT SPEECH ACTS - Sakinah, Hatfina (2015)
This study aims to investigate a three-year-old Indonesian boy's response to indirect speech acts. It focuses on the perlocutionary acts to indirect speech acts given by the subject based on the response performed by the subject in relation to rank of imposition (Rx), proposed by Brown and Levinson (1987) as well as kinds of perlocutionary acts which appear mostly. The data were collected by recording the conversations with the subject, and taking notes. This study reveals that the subject responds to indirect speech acts by accepting and rejecting, both verbally and nonverbally. The most commonly used response was nonverbal response by following directions given by the interlocutors. There are four types of verbal acceptance performed by the subject, namely giving advice, inviting, expressing wants, and asking permission. Meanwhile, in accepting nonverbally, the subject followed his interlocutor's direction. In addition to acceptance, the subject used three strategies in rejecting verbally, namely suggesting alternatives, direct refusal, and expressing wants; while persisting actions was performed to reject the indirect speech acts nonverbally. However, the subject sometimes mixed verbal and nonverbal responses, and there was also a response showing that the subject did not understand the indirect speech act performed by the interlocutor. The result of this study also found that ranking of imposition is the most influential factor that influences response to indirect speech acts performed by the subject. In heavy ranking of imposition, orders and prohibitions were rejected. However, the interlocutor's permission was allowed. Meanwhile, in light ranking of imposition, orders and prohibitions were accepted. The findings of this study suggests that at the age of three, this Indonesian boy has been able to respond to indirect speech acts given by his interlocutors in various speech situations as well as of different ranking of impositions. The subject seems to have mastered a certain level of pragmatic competence required to perform a given speech act.